Retrieval of sea surface temperature from INSAT-IB radiometer measurements using a multi -channel simulation approach - KELKAR, RR; TIWARI , VS; PRASAD, SANT (MAUSAM, 1989)
In the multi-channel sea surface temperature (MC SST) retrieval technique, brightness temperatures obtained from different satellite radiometer window channels viewing the same area are used to eliminate the atmospheric effects. The MC SST technique cannot be used with satellite radiometers having a single infrared window, e.g., INSAT-1.B \’HRR. In the present paper, a method has been proposed to split up the radiance received over a single channel, .10.5-12.5 /L, as a sum of two component radiances over .10.5- 11.5 and 11.5-12.5 /L bands parametrically in terms of the atmospheric water vapour content, thus allowing the MC SST algorithm to be applied if the water vapour content is known or assumed. The difference between MC SST and the single-window brightness temperature (Tsw) is defined interms of Tsw and the total atmospheric Water vapour content. Using climatological (IIOE) water vapour data, isotherms of INSAT-IB sea surface temperature over Arabian Sea, Bay of Bengal and Indian Ocean are presented for Jaruary and May. 1986. Comparison with NOAA retrievals shows good agreement. The method is meant for cloud-free areas.